PEMBUATAN PULP DENGAN MEMANFAATKAN LIMBAH KULIT DURIAN (DURIO ZIBETHINUS MURR) DENGAN CAMPURAN (RESINA COLOPHONIUM) GUNA MENCEGAH DEGRADASI LINGKUNGAN - Kurniawan W, Deddy Kurniawan W; Arifan, Fahmi; Adim, M. Dwi Khoirun (Vocational School Diponegoro University, 2013)
Deddy Kurniawan W, Fahmi Arifan, M. Dwi Khoirun Adim, in this article explain that paper is one of the primary needs for humans today . High paper usage is resulting increased in production of paper . On the other hand, paper which are usually made ​​from cellulose and hemi-cellulose in wood can result environmental degradation , due to the use of wood and tree felling leads to long-term basis that can increase the temperature of the earth surface ( global warming) . Durian is relatively abundant in Indonesia , durian shell contains high cellulose ( 50-60 % ) and lignin content ( 5 %), also a low starch content ( 5 % ) . Durian shell wastes containing fibre with dimensions of length and fiber thick wall that be able to bind well when given a synthetic adhesive or an adhesive mineral . Pulp which is produced from durian shell waste in experiments were 1 , 2 , 3 and 4, have a value of α - cellulose content of 35 % , 45 % , 27.7 % , 37.5 % and 57.6 %, respectively. When yield value of 49.2 % , 66.8 % and 48.2 % respectively. Keywords: pulp, durian, gondorukem, digester